Workers' participation in management - McCarthy, Charles (Statistical and Social Inquiry Society of Ireland, 1971)
It seems to me that it would be quite inappropriate to confine this paper to a discussion on the role of workers' representatives at top management level. Management is a function which occurs at all levels in a firm, from the activities of a firstline supervisor on the shop floor to those of a general manager. This is why so many people prefer the phrase industrial democracy, conveying the idea, as it does, of a lifestyle, a manner of approach, more profound than the particular and varying institutions which give it expression.
Read before the Society, 6 November 1970
Keywords: Worker participation in management; Employer - employee relations; Labour - management relations; 314.15